Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jad.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating family factors into treatment planning for adolescent depression: Perceived parental criticism predicts longitudinal symptom trajectory in the Youth Partners in Care trial

Abstract: Background: This study aimed to clarify the predictive significance of youth perceptions of parental criticism assessed using a brief measure designed to enhance clinical utility. We hypothesized that high perceived parental criticism would be associated with more severe depression over 18-months of follow-up. Methods:The study involved secondary analyses from the Youth Partners in Care trial, which demonstrated that a quality improvement intervention aimed at increasing access to evidencebased depression trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 68 publications
3
11
0
Order By: Relevance
“…First, negative family experiences, including parental criticism and family conflict, emerged as particularly relevant for depressive symptoms. This echoes previous research (Rapp et al, 2021 ), but further suggests that these effects are unique; that is, independent of factors like family support, these two types of negative family experience appear to pose distinct risks. On the other hand, although the association between conflict and depressive symptoms was in the expected direction, family conflict appeared to share a negative association with suicide risk after accounting for depressive symptoms (i.e., higher conflict was associated with lower risk), suggesting more complex processes worthy of further investigation (e.g., family detachment).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…First, negative family experiences, including parental criticism and family conflict, emerged as particularly relevant for depressive symptoms. This echoes previous research (Rapp et al, 2021 ), but further suggests that these effects are unique; that is, independent of factors like family support, these two types of negative family experience appear to pose distinct risks. On the other hand, although the association between conflict and depressive symptoms was in the expected direction, family conflict appeared to share a negative association with suicide risk after accounting for depressive symptoms (i.e., higher conflict was associated with lower risk), suggesting more complex processes worthy of further investigation (e.g., family detachment).…”
Section: Discussionsupporting
confidence: 84%
“…The opposite is also true: when adolescents and young adults experience conflict with their families and isolation from peers, this contributes to stress and impacts psychosocial functioning (Orben et al, 2020 ; Sheeber et al, 2001 ). Indeed, family and peer factors have been associated not only with the development of clinically-relevant symptoms (Prinstein et al, 2000 ) but also with treatment trajectories and outcomes (Baker & Hudson, 2013 ; Rapp et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that adolescents who perceived their closest relationships as more critical of them showed a stronger FC between brain areas linked to processing negative emotions, self-referential thinking and rumination when exposed to criticism. This concurs with the assumption that high PCM scores are a risk factor for poorer clinical course in depressed adults (14,15) and adolescents (16). Previous research has demonstrated that depressed adolescents display an even more pronounced activation of brain areas involved in encoding, retrieving, monitoring and/or evaluating emotionally salient information after exposure to parental (maternal) criticism than healthy adolescents (29,30).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it is not known whether the results found in adult samples would hold true in that younger age group, but emerging evidence seems to suggest that it could. In a recent longitudinal study reporting on a large out-patient adolescent sample, higher PCM scores proved predictive of continued clinical depression scores (16). These findings point to the crucial role exposure to and/or perception of criticism may play in (continued) vulnerability for psychopathology.…”
Section: Introductionmentioning
confidence: 87%